Students’ Speaking Ability Through Information Gap Activities At XI SMA Ekasakti Padang - Cut Natasya Hasany; Feby Meuthia Yusuf; Yessy Marzona (Kilau Publishing, 2026)
This study aims to analyze students' speaking ability through the use of the Information Gap technique in grade XI IPA students of SMA Ekasakti Padang. The background of this study is based on the fact that many students still experience difficulties in speaking English due to the fear of making mistakes and the lack of effective teaching strategies. This study focused on determining students' speaking ability using the Information Gap technique, identifying its strengths and weaknesses, and understanding the problems faced by students when speaking. The method used was descriptive with a quantitative approach, with a population of nine students, but only six took the speaking test due to health problems. Data were collected through speaking tests and analyzed using average and percentage formulas. The results showed that students' speaking ability through the Information Gap technique was classified as good with an average score of 75, although the main obstacle faced by students lay in the aspect of speaking fluency which obtained the lowest score compared to other aspects.